Conceptual modelling for simulation: Progress and grand challenges. Issue 1 (2nd January 2020) - Robinson, Stewart
ABSTRACT: In 2007, the Journal of Simulation ran the first ever journal issue dedicated to conceptual modelling for discrete-event simulation. The editorial for that issue reported on a 2006 meeting of conceptual modelling researchers that identified a set of research themes. Just over 10 years later, this paper reviews the progress that has been made in conceptual modelling through a timeline of key events and a review of the literature. It then sets out the grand challenges in conceptual modelling. Over the last 10 years, there has been significant activity on some research themes, especially conceptual modelling frameworks and conceptual model representation. There remain, however, many underexplored and unexplored themes as well as some emerging themes. There is much more work to be done in conceptual modelling. The grand challenges set out research areas that will be difficult to make progress in, but for which progress will have a significant impact.